Ethanol vapor treatment of ‘laetitia’ plums stored under modified atmosphere Vapor de etanol durante o armazenamento de ameixas ‘laetitia’ em atmosfera modificada - Nunes F.R.* (2019)
© 2019, Sociedade Brasileira de Fruticultura. All rights reserved.The objective of this work was to evaluate the effect of ethanol vapor during storage in modified atmosphere on the ripening and maintenance of the postharvest quality of ‘Laetitia’ plums. The plums were obtained from an orchard in the municipality of Lages, SC. The experimental design adopted was completely randomized. The treatments evaluated were ethanol vapor doses (0, 2, 4, 6 and 8 mL kg-1 of fruit). The fruits were stored at 0.5±0.2°C and 92±2% RH for 30 days. Upon their removal from storage followed by another three days in room conditions (20±5ºC and 63±2% RH), the fruits were evaluated in relation to their physical and chemical attributes, incidence and intensity of internal browning, quantification of ethanol, acetaldehyde and ethyl acetate, and the activity of enzymes peroxidase and superoxide dismutase. The application of ethanol vapor was efficient in maintaining the fruits flesh firmness, reducing the evolution of the red coloring, and resulted in greater activity of enzymes peroxidase and superoxide dismutase. However, the doses evaluated were not efficient in reducing the internal browning.